The influence of Pahang heritage food on behavioural intentions among Malaysian domestic tourists - Saad, Mazni; Kamarizzaman, Nur Assyiqin; Ishak, Noriza; James Pratt, Thomas (e-International Publishing House, Ltd., UK, 2021)
This study investigated how domestic tourists perceive Malaysian heritage food and how this may influence behavioral intentions. A survey was distributed through social media applications, and 164 tourists responded, with three being international, which were then discarded. In this study, correlation and regression analyses are used to analyze the responses and found that a positive and significant influence exists between emotional value, quality value, epistemic value, and a domestic tourist’s behavioral intentions to consume heritage foods. This study helps expand the understanding of Pahang’s heritage food's consumption value elements and its influence on the domestic tourists' behavioral intentions.